A mutation in the glutamate-rich region of RNA-binding motif protein 20 causes dilated cardiomyopathy through missplicing of titin and impaired Frank–Starling mechanism. Issue 1 (5th August 2016) - Beqqali, Abdelaziz; Bollen, Ilse A.E.; Rasmussen, Torsten B.; van den Hoogenhof, Maarten M.; van Deutekom, Hanneke W.M.; Schafer, Sebastian; Haas, Jan; Meder, Benjamin; Sørensen, Keld E.; van Oort, Ralph J.; Mogensen, Jens; Hubner, Norbert; et al.
Abstract: Aim: Mutations in the RS-domain of RNA-binding motif protein 20 (RBM20) have recently been identified to segregate with aggressive forms of familial dilated cardiomyopathy (DCM). Loss of RBM20 in rats results in missplicing of the sarcomeric gene titin ( TTN ). The functional and physiological consequences of RBM20 mutations outside the mutational hotspot of RBM20 have not been explored to date. In this study, we investigated the pathomechanism of DCM caused by a novel RBM20 mutation in human cardiomyocytes. Methods and results: We identified a family with DCM carrying a mutation (RBM20 E913K/+ ) in a glutamate-rich region of RBM20. Western blot analysis of endogenous RBM20 protein revealed strongly reduced protein levels in the heart of an RBM20 E913K/+  carrier. RNA deep-sequencing demonstrated massive inclusion of exons coding for the spring region of titin in the RBM20 E913K/+  carrier. Titin isoform analysis revealed a dramatic shift from the less compliant N2B towards the highly compliant N2BA isoforms in RBM20 E913K/+  heart. Moreover, an increased sarcomere resting-length was observed in single cardiomyocytes and isometric force measurements revealed an attenuated Frank–Starling mechanism (FSM), which was rescued by protein kinase A treatment. Conclusion: A mutation outside the mutational hotspot of RBM20 results in haploinsufficiency of RBM20 . This leads to disturbed alternative splicing of TTN, resulting in a dramatic shift to highly compliant titin isoforms and an impaired FSM. These effects may contribute to the early onset, and malignant course of DCM caused by RBM20 mutations. Altogether, our results demonstrate that heterozygous loss of RBM20 suffices to profoundly impair myocyte biomechanics by its disturbance of TTN splicing.